Image restoration using sparse dictionary - Tai, Ivan Wei Zhong (2019)
Image restoration using sparse dictionary as the title says is the method of restoring damaged/lost parts back to the original image using a sparse dictionary. Also, to remove noise from an image to try and recover the original image as much as possible. This project is mainly using Matlab to create an image restoration algorithm based on sparse signal processing and compressed sensing. Matlab designs of sparse dictionary and algorithms will help to achieve the denoising of the images.